The Concept of Tazkiyatunnafs in the Book of Ihya 'Ulumuddin and Its Implications in Sufistic Counseling - Nurzaman, Muhamad Rizal; Solahudin, Dindin; Fajar, Dadang Ahmad (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
The moral and spiritual crisis has triggered a degradation of human morals in modern times, leading counselors to seek a more holistic approach that not only addresses behavior but also delves into the deepest aspect of human beings, namely the soul (nafs). Therefore, Al-Ghazali's thoughts on soul purification, which focus on morals, are increasingly relevant. His holistic approach, which combines cognitive, emotional, and spiritual aspects, offers a comprehensive solution to address complex moral problems. This study aims to formulate the concept of tazkiyatunnafs in Imam Al-Ghazali's book Ihya Ulumuddin and to simulate the implications of the concept of tazkiyatunnafs if applied in Sufi counseling that focuses on moral guidance. This research uses a qualitative method, with data collection techniques using a literature study approach (library research), observation, and content analysis of guidance messages in the book that focuses on qualitative data analysis. The research paradigm is built with the grand theory of tazkiyatunnafs, Sufi counseling, and moral guidance. Based on the research results, it is concluded that the concept of tazkiyatunnafs from the perspective of Imam Al-Ghazali focuses on moral development that is oriented towards mujahadah and riyadhoh. The stages of tazkiyatunnafs proposed by him consist of three stages, namely takhalli (purifying oneself from bad character), tahalli (filling the soul with good character), and tajalli (the manifestation of God in the human self through the reflection of divine attributes in the human self). And the implications of tazkiyatunnafs, developing human potential as creatures of God whose task is to lead themselves fully to worship only God, and to base all their behavior on the basis of achieving His pleasure.